Efficacy of proportional condylectomy in a treatment protocol for unilateral condylar hyperplasia: A review of 73 cases. Issue 7 (July 2017) - Mouallem, Guillaume; Vernex-Boukerma, Zahia; Longis, Julie; Perrin, Jean-Philippe; Delaire, Jean; Mercier, Jacques-Marie; Corre, Pierre
Abstract: Introduction: Unilateral condylar hyperplasia (UCH) is characterized by an excessive growth of a mandibular condyle, resulting in facial, and occlusal deformities. Scintigraphic hyperactivity usually triggers the need of condylectomy. Delaire has presented a protocol for the treatment of active or non-active UCH using systematically a proportional condylectomy, which could solve both aetiology and adaptive deformities. The aim of this study was to evaluate this protocol by clinical and radiographical analysis. Materials and methods: Seventy-three patients with UCH were included in this retrospective study, and divided by clinical and cephalometric analysis in vertical, or transversal forms of UCH according to Delaire's classification. All patients were treated with 'proportional condylectomy', any indicated orthognathic procedures, along with maxilla-mandibular elastic therapy, and rehabilitation. Architectural, aesthetical, occlusal, and functional features were evaluated using clinical, cephalometric, and photographic measurements both preoperatively, and at the end of the follow-up. Results: A female predominance was observed (65.8%). Vertical forms were more represented than transversal forms (61.6% versus 38.4%). There was a significant improvement of the occlusal plane, the posterior vertical excess, the chin deviation and the soft-tissue features (p < 0.0001), regardless of the preoperative scintigraphic activity status (p < 0.0001). The occlusion, and temporo-mandibular joint (TMJ) functions was considered as normal in respectively 72.7%, and 93% of the patients. Conclusion: The results of this study have demonstrated that a protocol using a 'proportional condylectomy', any indicated orthognathic techniques, maxilla-mandibular elastic therapy, and rehabilitation, is a reliable option for treating UCH, regardless the activity status of the pathology.